If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -8 = -16 + 3n Reorder the terms: -8 + 7n = -16 + 3n Solving -8 + 7n = -16 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -8 + 7n + -3n = -16 + 3n + -3n Combine like terms: 7n + -3n = 4n -8 + 4n = -16 + 3n + -3n Combine like terms: 3n + -3n = 0 -8 + 4n = -16 + 0 -8 + 4n = -16 Add '8' to each side of the equation. -8 + 8 + 4n = -16 + 8 Combine like terms: -8 + 8 = 0 0 + 4n = -16 + 8 4n = -16 + 8 Combine like terms: -16 + 8 = -8 4n = -8 Divide each side by '4'. n = -2 Simplifying n = -2
| 5x(x+7)=20 | | -3(x-2)+4(2x+5)=10x-(5x-23) | | x+7+z=-11 | | -20-7x=16+9x | | 90x=585 | | 36-14x=8 | | 5x=4+-4+5x | | 20(5)=20q+5 | | 8n-2=19+5n | | 6t-12-(3t-3)=-19 | | 2(x-1)+3(x+2)=5x+4 | | 2(2x)+47=2(2x)+47 | | -40+3x=10+2x | | 6x-12=5x+17 | | 6(y-24)-6y=0 | | -40+3x=2x | | 4*x-17=23 | | 4x+x^2=179 | | 6-x=10-2x | | 4y+4x=12 | | 2x+x+2(2)+75=180 | | 20=16(16)+b*b | | 11x-66=7x+34 | | 5gf^2+g^2f+15gf= | | 9(2p-1)= | | 9t=-2t^3-9t^2 | | 4y^2-18y+21=0 | | 7x+18=4x+30 | | 43-[4+9y-3(y+5)]=-5(2y+3)-[6(y-1)-3y+2] | | 31792.5=3.14*r^2 | | 36=-4(x-3) | | 2n^2=-24-19n |